A fluorogenic probe for tracking GSH flux in developing neurons. Issue 4 (11th December 2019) - Zong, Haichao; Peng, Jiayi; Li, Xiao-Rong; Liu, Meng; Hu, Yongzhou; Li, Jia; Zang, Yi; Li, Xin; James, Tony D.
Abstract : We have developed an ultrasensitive assay for GSH in order to help uncover its role in neuronal development. Abstract : Understanding GSH flux in developing neurons is prerequisite to reveal its role in neuronal development but necessiates an ultrasensitive assay. By systematically exploring key structural factors determing probe sensitivity in live cells, we developed a fluorogenic probe capable of imaging subtle GSH fluctuations in developing neurons.